1979
DOI: 10.1007/bf01888921
|View full text |Cite
|
Sign up to set email alerts
|

Distribution ofα 1 phenotypes in Japanese: Description of Pi M subtypes by isoelectric focusing

Abstract: SummarySerum a~-antitrypsin phenotypes were determined by polyacrylamide gel slab isoelectric focusing in a sample from 1,271 unrelated healthy Japanese living in Tokyo. Three common Pi M subtypes (MIM~, M1M~ and M2M2) were found, and the allele frequencies estimated (Pim= 0.83, Pi~Z=0.17) were found to be similar to those observed in the European populations. A large Z ~ value, however, may indicate the presence of further microheterogeneity among Pi M subtypes. In contrast with Pi M subtypes, rare variants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 13 publications
(10 reference statements)
1
10
0
Order By: Relevance
“…This allele could be similar to PiNhampton described by Arnaud et aL (1978), though no direct comparison has been made. The frequency of this mutant was very similar to the data published by Miyake et aL (1979). This experience enables us to consider this allele to be present in other Asiatic populations.…”
Section: Crl-antitrypsin (Pi)supporting
confidence: 87%
See 2 more Smart Citations
“…This allele could be similar to PiNhampton described by Arnaud et aL (1978), though no direct comparison has been made. The frequency of this mutant was very similar to the data published by Miyake et aL (1979). This experience enables us to consider this allele to be present in other Asiatic populations.…”
Section: Crl-antitrypsin (Pi)supporting
confidence: 87%
“…The most recent data were published by Miyake et al (1979). In this study four PiM subtypes were observed.…”
Section: Crl-antitrypsin (Pi)mentioning
confidence: 59%
See 1 more Smart Citation
“…No Z deficient variant has been reported from Asian countries (14)(15)(16)(17). One null variant, QOhongkong (a two-nucleotide deletion at residue 3 18) was reported in a Chinese family (8).…”
Section: Discussionmentioning
confidence: 99%
“…With the aid of IEF technique we have also checked whether abnormal extrabands [17] appear in the pattern of the ot|AT pheno type during acute viral hepatitis. In no in stance have we noticed this phenomenon, the bands at IEF being identical after recovery and always consistent with those of the par ents.…”
Section: Discussionmentioning
confidence: 99%